2015
DOI: 10.1080/19443994.2014.911118
|View full text |Cite
|
Sign up to set email alerts
|

Formation of pre-coating dynamic membrane on mesh filter by cross-flow filtration of PAC–water suspension in a bioreactor: experimental and modeling

Abstract: A B S T R A C TThis study presents a closed-loop process for forming pre-coated dynamic membrane used in membrane bioreactor. Powder-activated carbon (PAC) particles are suspended by using axial-flow agitator whilst simultaneously deposited upon the filter medium by cross-flow filtration. The revolution speed of agitator is varied in the range of 150-450 rpm. Computational fluid dynamic is used to calculate velocity and shear rate adjacent to membrane surface. The force balance of the particles considers the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…With the aid of CFD simulation, local parameters, which are difficult to measure experimentally, can be calculated. Several inclusive studies can be found on the CFD simulation of MBRs, [9][10][11][12][13][14][15][16][17][18][19] airli bioreactors, 20,21 stirred tank reactors, 22,23 and bubble columns. 24,25 In an MBR, aeration is the main mixing mechanism; 10 hence, optimization of mixing characteristics affects the energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of CFD simulation, local parameters, which are difficult to measure experimentally, can be calculated. Several inclusive studies can be found on the CFD simulation of MBRs, [9][10][11][12][13][14][15][16][17][18][19] airli bioreactors, 20,21 stirred tank reactors, 22,23 and bubble columns. 24,25 In an MBR, aeration is the main mixing mechanism; 10 hence, optimization of mixing characteristics affects the energy consumption.…”
Section: Introductionmentioning
confidence: 99%